Communication, Sense of Community, and Disaster Recovery: A Facebook Case Study - Paton, Douglas; Irons, Melanie (Frontiers in Communication, 2016)
Disasters create an urgent need for people to deal with novel emergent problems. To respond effectively, people require information (about the event, support resources, actions etc.) and the ability to interpret and use available information to deal with diverse, emergent hazard consequences and demands over time. This diversity renders top-down, homogenous approaches to disaster communication ineffective. This paper examines whether a social media-based communication strategy, using Facebook, represents a more effective way of accommodating this diversity (e.g., event impacts, geographical, demographic, social), meeting the information needs of affected populations, and enhancing the quality of disaster communication. Data on how 583 people who used a Facebook page (Tassie Fires - We Can Help) specifically developed to assist response and recovery for the 2011 Tasmanian wildfire/bushfire disaster were obtained using an open-ended questionnaire. The accounts of people’s experience of the event and their engagement with the Facebook page obtained from their responses to the questionnaire were analysed using thematic analysis. The paper also discusses evidence regarding how the development of functional social relationships amongst those who engaged via the page enhanced the effectiveness of the disaster communication process. In particular, it discusses how engagement with the page and the way the page was managed by the Administrator facilitated the development of Sense of Community, a social structural characteristic known to influence the quality of disaster communication. The paper concludes with a discussion of the implication of the findings for future research into the relationship between Facebook use, disaster communication and disaster recovery.